What do new graduate nurses really need when transitioning to clinical roles? - Hadi Jafarimanesh; Shahrzad Ghiyasvandian; Masoumeh Zakerimoghadam (Canadian Medical Education Journal)
Background: Transitioning from a student nurse to a clinical nursing role is a critical period for newly graduated nurses (NGNs), often accompanied by multiple challenges. Understanding their professional needs during this transition is essential for designing targeted supportive interventions that enhance adaptation, professional integration, and workforce retention. In this study, we aimed to explore the perceived needs of NGNs during their transition to clinical nursing roles in medical and surgical wards.